Rozszerzenie i kurczenie zakresu działalności przedsiębiorstwa jako podstawowe etapy ewolucji jego strategii - Banaszyk, Piotr (Expanding and Shrinking the Range of a Company Activity as Its Strategy Evolution Basic Stages, 2008)
The explanation of the company strategy evolution is the main goal of the article. Progress in the discipline of information and communication technology is the explanation factor. This approach enables to reduce the company strategy evolution to two stages: expanding and shrinking of business activity range.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 21-29